Hernia Nucleus Pulposus: Pathophysiology, Risk Factors, and Clinical Management – A Literature Review - Luluk Hermawati; Maytia Pratiwisitha; Maulana Hasymi Hutabarat; Ghea Farmaning Thias Putri; Ratno Susanto; Omat Rachmat (International Journal of Cell and Biomedical Science, 2026)
Background: Lumbar Herniated Nucleus Pulposus (HNP) is a leading cause of low back pain and radicular symptoms that significantly impair functional capacity and quality of life. The condition arises from a complex interaction of biomechanical stress, inflammatory responses, and degenerative biological changes in the intervertebral disc. This article aims to comprehensively review current evidence on the pathophysiology, risk factors, and clinical management of lumbar HNP using a narrative literature review approach.. Methode: A literature search was conducted across PubMed, Google Scholar, and accredited national journals using the keywords “hernia nucleus pulposus,” “lumbar disc herniation,” “low back pain,” “pathophysiology,” and “clinical management.” Eligible articles were full-text publications in English or Indonesian published between 2015 and 2025, including original research, literature reviews, systematic reviews, and clinical practice guidelines. Studies related to traumatic or non-lumbar disc herniation and those without full-text availability were excluded. Selected articles were analyzed descriptively and synthesized narratively. Results: The review indicates that lumbar HNP is a progressive degenerative disorder influenced by altered disc biomechanics, inflammatory cascades, and cellular aging. Major risk factors include advancing age, increased body mass index, sedentary lifestyle, and occupational exposure to heavy physical workload. Clinical management follows a stepwise strategy, prioritizing conservative therapy, while surgical intervention is reserved for selected cases. Conclusion: A comprehensive understanding of the pathophysiological mechanisms and associated risk factors of lumbar HNP is essential to support evidence-based and individualized patient management.